Pengaruh Pembiasaan Tadarus Dhuha Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Qur’an Hadits Di Mts Gunung Putri Bogor - Alam, Mufassirul; Alwi, Wildan; Sarif, Muhamad (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2024)
This research is a field research, while the research approach is a quantitative approach, meaning that the objectivity of the research design is carried out using statistical processing of numbers, structures and controlled experiments. Judging from the population and sample, this research is a population research, because it involves all research subjects, namely class VIII. The data collection technique uses documentation of questionnaire distribution. The data obtained were analyzed using quantitative statistics. Habit of Dhuha Recitation on Student Learning Motivation in the Qur'an Hadith Subject at Mts Gunung Putri Bogor in the 2023/2024 Academic Year. In the good category. This can be seen from the analysis of the Habit of Dhuha Recitation of Class VIII Students at MTs Gunung Putri Bogor in the 2023/2024 Academic Year with a good category. Based on the distribution of the questionnaire style carried out by the researcher on the correlative quantitative analysis of the results of the study showed that there was an influence between the Habit of Dhuha Recitation on Student Learning Motivation in the Qur'an Hadith Subject at Mts Gunung Putri Bogor in the 2023/2024 Academic Year. On students' learning motivation in the subject of Qur'an Hadith class VIII MTs Gunung Putri Bogor. This is proven by the analysis of the regression test Based on the description above Sig 0.005 <0.05 and tcount 2.949 and ttable with a significance level of 5%, namely 2.008. So it can be said that tcount> ttable, namely 2.949> 2.008 so that Ho is rejected and Ha is accepted. The results of this study are expected to contribute knowledge for teachers, students, parents, MTs and others that the habit of Tadarus Dhuha can affect students' learning motivation.